Capillary water absorption in cracked and uncracked mortar – A comparison between experimental study and finite element analysis. (1st May 2016) - Van Belleghem, B.; Montoya, R.; Dewanckele, J.; Van den Steen, N.; De Graeve, I.; Deconinck, J.; Cnudde, V.; Van Tittelboom, K.; De Belie, N.
Highlights: Gravimetrical evaluation of capillary water absorption in sound and cracked mortar. Use of Finite Element Method to simulate capillary water entrance in cracked mortar. Use of X-ray radiography for visualization of water movement in mortar. Good to excellent agreement between experimental results and numerical modeling. Abstract: The durability and service life of concrete structures strongly depends on the transport of fluids through the cementitious material. These fluids can contain aggressive agents which causes degradation of the concrete matrix and corrosion of the steel reinforcement. In most cases the dominating mechanism for water ingress in cementitious materials is capillary absorption, especially when cracks are present. To be able to predict the durability of a concrete structure containing cracks, it is necessary to know the distribution of water and other aggressive agents inside the cementitious material. Capillary water entrance in uncracked and cracked mortar was simulated in this research by solving the 3D Richard's equation using Finite Element Method. Realistic boundary conditions, by considering the water evaporation process, were imposed in the model. The developed numerical model was validated by performing gravimetrical water absorption experiments and X-ray radiography on mortar specimens with one or multiple artificial cracks. This paper reports the validation of the numerical model through an experimental program. The numerical results agreed well with the experimental results in both the transient global water content and the transient water distribution for both uncracked and cracked mortar. Therefore, the imposed boundary conditions correctly describe the water uptake phenomenon. To be able to completely describe the durability of cementitious materials, the numerical model still has to be extended regarding the ingress of other substances like CO2 and chlorides.